Footstep power generation/ Adriana Noh ...[et al.] - Noh, Adriana; Mohammad Nor, Muhammad Amir Syakir; Rosli, Muhammad Arif; Aris, Mohd Aziz (2018)
Nowadays, energy and power are one of necessities in this modern world. As the demand of energy is increasing, the ultimate solution is by implementing the renewable sources of energy by designing Footstep Power Generation. It is designed to be very useful at places such as universities, office and others. By using footstep power generation design, the project will be able to show how a simple mechanical motion could be converted into electrical power. When a person walks, energy is lost in the form of vibration. The pressure exerted can be converted from mechanical energy to electrical energy. This system could store the electrical energy in the 6V rechargeable battery and the display the voltage of the battery on LCD by using Arduino Uno. The power produced can be utilized by lighting up lights along the corridors or emergency power failure situations.